«A Lima for all»: The Huaycán housing program and the United Left’s urban policy, 1983-1985 - Luna-Victoria Indacochea, Lucía (2022)
In 1984, in the context of Peru’s internal armed conflict between the Shining Path and the State (1980-2000), Lima’s socialist mayor Alfonso Barrantes Lingán decreed the creation of Huaycán, the first housing project targeting Lima’s poorest residents. Huaycán originated from a shared socialist vision by urbanists and shantytown settlers to address the politics of abandonment by establishing a co-management program between municipal representatives and the population. This article traces the creation of Huaycán, from 1983 to 1985, as a project that emanated from the demands of a new generation of urban residents. The article reveals the tensions derived from within the leftist front, and between the urbanists and shantytown settlers that created the project.